Impact of coastal upwelling dynamics on the pCO2 variability in the southeastern Arabian Sea. (April 2022) - Ghosh, Jayashree; Chakraborty, Kunal; Bhattacharya, Trishneeta; Valsala, Vinu; Baduru, Balaji
Highlights: Upwelling-driven DIC enhancement is more in the near-surface waters than its removal by net biological processes in SEAS. Biology-driven changes are notable only in the southern part of SEAS but not significant in controlling pCO2 variability. Difference between the annual mean depth of DIC-cline and nitracline does not significantly vary in SEAS. Upwelling-driven physical changes dominate over the enhanced biology-driven changes in inducing pCO2 seasonality in SEAS. Abstract: The southeastern Arabian Sea (SEAS) experiences moderate to weak upwelling along the southwest coast of India during the southwest monsoon (SM). The coastal upwelling initiates from mid-May along the southern-most tip of India, and with the advancement of SM, it propagates towards the northern latitude. This study examines the impact of coastal upwelling dynamics on the spatio-temporal variability of pCO2 in SEAS. It aims to identify the factors controlling the variability of pCO2 using high-resolution, regional ocean-ecosystem model-simulated outputs while available in situ and ship-based observations are used to establish the capability of the model. The cold deeper water that rises to the surface during upwelling decreases surface ocean pCO2 by 50 ± 2.4 µatm, whereas the presence of carbon-rich upwelling waters to a significantly shallower depth increases pCO2 by 52 ± 1.5 µatm of SEAS during SM. The salinity component increases surface ocean pCO2 by 2.0 ± 1.6 µatm. It has relatively less impact when compared with the individual effects of temperature and dissolved inorganic carbon components in controlling surface ocean pCO2 variability. The biological activities are profound only in the southern part of SEAS where biology-driven changes decrease surface ocean pCO2 by 4.0 ± 0.4 µatm during SM. The total biology-driven changes consist of both soft and hard tissues decrease the pCO2 level of SEAS by 2.0 ± 0.2 µatm during SM. Therefore, the upwelling-driven physical dynamics dominate the biological processes in controlling the spatio-temporal variability of surface ocean pCO2 in SEAS during SM, which contrasts the physical-biological dynamics of the sea east of Sri Lanka, where the biological processes dominate over physical dynamics in controlling surface ocean pCO2 variability.